2002
DOI: 10.1177/002215540205001208
|View full text |Cite
|
Sign up to set email alerts
|

Lac z Histochemistry and Immunohistochemistry Reveal Ephrin-B Ligand Expression in the Inner Ear

Abstract: S U M M A R YImmunostaining in transgenic mice carrying the lac z gene can be used to map gene and protein distribution in a single tissue. In this study, we examined inner ears from ephrin-B3 homozygous and ephrin-B2 heterozygous mice. Ephrin-B3 lac z expression was limited in these mice. However, immunostaining revealed ephrin-B3 throughout cochlear and vestibular regions. Immunoreactivity was absent in ephrin-B3-homozygous null mutants, demonstrating the specificity of the antibody. Ephrin-B2 lac z reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Cochleae were decalcified in 5% EDTA for three days at 4°C, washed in rinse buffer (0.01% sodium deoxycholate, 0.02% Nonidet P-40, 2 mM magnesium chloride in PBS) for 1 hour and stained in 1 mg/ml X-gal/5 mM potassium ferrocyanide/5 mM potassium ferricyanide in rinse buffer overnight at 37°C (Bianchi, et al, 2002; Corradi, et al, 2003). Cochleae were dissected for whole-mount preparation or processed further for sections; Cochleae were cryoprotected in 20% sucrose overnight at 4°C before embedding in Tissue-Tek O.C.T.…”
Section: Methodsmentioning
confidence: 99%
“…Cochleae were decalcified in 5% EDTA for three days at 4°C, washed in rinse buffer (0.01% sodium deoxycholate, 0.02% Nonidet P-40, 2 mM magnesium chloride in PBS) for 1 hour and stained in 1 mg/ml X-gal/5 mM potassium ferrocyanide/5 mM potassium ferricyanide in rinse buffer overnight at 37°C (Bianchi, et al, 2002; Corradi, et al, 2003). Cochleae were dissected for whole-mount preparation or processed further for sections; Cochleae were cryoprotected in 20% sucrose overnight at 4°C before embedding in Tissue-Tek O.C.T.…”
Section: Methodsmentioning
confidence: 99%
“…Whole-mount staining for ␤-Gal in LYVE-1 ϩ/Ϫ and LYVE-1 Ϫ/Ϫ mice and tumor cryostat sections was performed as described previously (2). For whole-mount preparations of dermal lymphatics, ear tissues were fixed overnight in 4% paraformaldehyde in phosphate-buffered saline (PBS), and the dorsal segment was blocked for 3 h in 30 mg/ml milk powder-10% fetal bovine serum (FBS) in PBS-0.1% (wt/vol) Triton X-100 prior to double staining overnight with rat anti-mouse CD31 (MEC 13.3)/ Alexa594-conjugated goat anti-rat and hamster anti-mouse podoplanin (8.1.1)/ Alexa488-conjugated goat anti-hamster antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Eph proteins, including the Eph receptors and their ligands, the ephrins, are broadly expressed in the developing auditory system (for reviews see Bianchi et al, 2002, Pickles, 2003, Cramer, 2005, Gabriele et al, 2011). They provide multiple mechanisms for signaling and for generating precise connectivity.…”
Section: Eph Receptors and Ephrinsmentioning
confidence: 99%
“…Several studies have demonstrated that Eph receptors and ephrins are expressed in the developing inner ear in mice (Henkemeyer et al, 1994, Bianchi and Gale, 1998, Bianchi et al, 2002, Pickles et al, 2002, Zhou et al, 2011, Coate et al, 2012, Defourny et al, 2013). SGNs express ephrin-B1 and ephrin-B2, and growth of SGN processes is inhibited in vitro by EphB2 through reverse signaling (Bianchi and Gray, 2002, Zhou et al, 2011).…”
Section: Peripheral Auditory Pathwaysmentioning
confidence: 99%